Análise da convexidade da relação entre desempenho e captação de fundos multimercados brasileiros - Andrade, Vívian Barja Fidalgo Silva de (2015)
The objective of this work is to verify the hypothesis of convexity in the relationship between performance and funding in the Brazilian multimarket investment funds industry from 2000 to 2013. A total of 4,547 multimarket funds were analyzed, with a minimum of 6 months of existence. Due to the size of the category, we also observe how this relationship is in the subcategories and in two moments: before and after the crisis of 2008. As results, we find a more elastic relationship the higher the performace, corroborating the hypothesis raised. We also show evidence that the crisis had no significant impact on the convexity of the curve.